Abuse of Authority by Village Head in Cases of Sexual Violence against Women - Rizky, M. Affan; Dewi, Erna; Budiyono, Budiyono (Faculty of Law, Universitas Lampung, 2024)
The government's efforts to combat sexual violence in society are embodied in the Law on the Elimination of Sexual Violence, reflecting the State's responsibility to protect and improve the psychological well-being of victims, whether they have experienced physical or psychological harm. Protection of women in the workplace is crucial, and ensuring their rights is a legal imperative. The prevalence of sexual violence against women in work environments, often driven by power imbalances, highlights the urgent need for effective legal protection. This research aims to examine the influence of power relations on sexual violence crimes committed by regional officials and to identify optimal legal protections for women who are victims of sexual violence. Employing a normative juridical approach, the research finds that while existing laws are generally adequate for addressing sexual violence, their implementation falls short of expectations. Recommendations include enhancing legal protection to be more victim-centered, as current regulations primarily focus on penalizing perpetrators. There is a need for policies that provide comprehensive protection and justice for female victims of sexual violence.